The People of God in the Apocalypse : discourse, structure, and exegesis - Pattemore, Stephen (Monograph series (Society for New Testament Studies), 2004)
This book examines how the original audience of the Apocalypse would have heard themselves portrayed in the visions of chapters 4 22, and in what directions it would have motivated them. Stephen Pattemore uses linguistic analysis to help understand Revelation in the context of other biblical and non-biblical texts.